1975
DOI: 10.1530/jrf.0.0430241
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Assessment of the Source of Oestrogen Within the Ovary of the Domestic Fowl, Gallus Domesticus

Abstract: Summary. Oestradiol was measured by radioimmunoassay in blood draining individual preovulatory follicles and in different ovarian tissues of the hen. The concentration of oestradiol in blood from follicles 20 to 50 hr before ovulation ranged from 66 to 264 pg/ml and was less than that in peripheral blood collected concurrently, suggesting a net uptake rather than secretion of oestradiol by the follicle at these times.In one bird approximately 6 hr before ovulation, the highest content of oestradiol in tissue (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 15 publications
(20 reference statements)
2
16
0
Order By: Relevance
“…The primary source of oestrogen in the hen ovary is the thecal layer of small prehierarchical follicles (Senior & Furr 1975, Robinson & Etches 1986) which, as reported here, have detectable mRNA expression of all activin receptor subtypes. Furthermore, addition of oestradiol to cultured laying hen granulosa cells from small yellow follicles and large white follicles increased follistatin and activin B-subunit mRNA expression, with no increase in immunoreactive -subunit protein (Davis et al 2000), suggesting that theca-derived oestrogen may regulate granulosa inhibin B, or possibly activin B production in prehierarchical follicles.…”
Section: Discussionsupporting
confidence: 69%
“…The primary source of oestrogen in the hen ovary is the thecal layer of small prehierarchical follicles (Senior & Furr 1975, Robinson & Etches 1986) which, as reported here, have detectable mRNA expression of all activin receptor subtypes. Furthermore, addition of oestradiol to cultured laying hen granulosa cells from small yellow follicles and large white follicles increased follistatin and activin B-subunit mRNA expression, with no increase in immunoreactive -subunit protein (Davis et al 2000), suggesting that theca-derived oestrogen may regulate granulosa inhibin B, or possibly activin B production in prehierarchical follicles.…”
Section: Discussionsupporting
confidence: 69%
“…Follicles (small white follicles) produced by the ovary are the major sources of oestrogen, producing over 80% of the total ovarian oestrogen (Senior and Furr, 1975;Armstrong, 1984;Nitta et al, 1991). Oestrogen from ovarian follicles is also responsible for the growth of the reproductive tract (Campbell et al, 2003), while progesterone, a major steroid hormone is secreted by the granulose cells of large ovarian hierarchical follicles (F 1 -F 3 ) of laying hens (Huang et al, 1979;Barh et al, 1983;Porter et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…small yellow follicles, large white follicles and large yellow follicles) produced by the ovary are critical to endocrinological balance and robust reproductive activities of female poultry. The main sources of ovarian E 2 are small white follicles and ovarian stroma with numerous cortical follicles containing more than 50% of ovarian aromatase activity and producing more than 80% of ovarian oestrogen (Senior and Furr, 1975;Armstrong, 1984;Nitta et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Rothchild & Fraps (1944a, b) postulated a hormonal secretion from the POF, and it has been claimed that injections of POF homogenate affect oviposition (Tanaka & Nakada, 1974). Earlier studies showed that steroid dehydrogenase activity was present in the granulosa cells of the POF (Wyburn & Baillie, 1966), and Furr (1969) and Senior & Furr (1975) reported on the progesterone and oestrogen content, respectively, of the POF.…”
Section: Introductionmentioning
confidence: 99%